A novel Q−PQV bus pair method of biomass DGs placement in distribution networks to maintain the voltage of remotely located buses. (1st March 2020) - Barik, Soumyabrata; Das, Debapriya
Abstract: This paper proposes a new DG placement and sizing technique by introducing a novel Q − P Q V bus pair in distribution networks (DNRs) with seasonal variation of load demand. The principle aim of this paper is to boost and maintain the voltage of remotely located buses to predefined optimal level for seasonal load demand by integrating biomass DGs in DNRs. The selection of locations and sizes of DGs is determined by novel bus pair, which is different from conventional buses present in power system studies. For P Q V bus along with active and reactive power, the voltage magnitude also is known, whereas, for Q bus, only reactive power is known. The power injection of Q bus with the load connected determines DG sizes. The inclusion of this new bus pair modifies the load flow technique, which is also given in the paper. The proposed methodology is applied on 33 bus DNR, while active power loss is taken as principal objective function. Both upf and lpf DGs are considered in this paper, and the results are compared with existing methods available in literature. The cost-benefit analysis shows the profit gained from it. Highlights: This work is based on the development of an algorithm to improve and maintain the voltage of remotely located buses. A novel concepts of Q-PQV bus is proposed and developed. Both the unity power factor and lagging power factor DGs are placed and sized optimally with seasonal load pattern. Techno-Economic analysis of the modified distribution system is studied after the placement of the DGs. The algorithm is tested on 33 bus distribution networks.